2018
DOI: 10.1111/apt.14812
|View full text |Cite
|
Sign up to set email alerts
|

Risk of diabetes in HIV‐infected patients is associated with cirrhosis but not with chronic HCV coinfection in a French nationwide HIV cohort

Abstract: Our study shows that in the HIV population, cirrhosis is associated with an increased occurrence of DM, but not chronic HCV infection or duration of HCV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Furthermore, we found that diabetes onset was independently associated with the liver fibrosis stage. These results are in line with those observed in other HIV cohorts [14,15]. On this point, in a large French multicentre cohort, cirrhotic patients had a 2-fold increased risk of developing diabetes but not patients with CHC [15].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, we found that diabetes onset was independently associated with the liver fibrosis stage. These results are in line with those observed in other HIV cohorts [14,15]. On this point, in a large French multicentre cohort, cirrhotic patients had a 2-fold increased risk of developing diabetes but not patients with CHC [15].…”
Section: Discussionsupporting
confidence: 90%
“…As both can fluctuate over time with and without cART, our focus was on the last 24 months of follow-up when most PLWH were under effective treatment. The occasional viremia (viral blips), defined by plasma VL ≥200 RNA copies/ ml, is well expected, and at least one other longitudinal study (a French HIV-1 cohort) has reported that detectable VL is associated with a modest risk for incident T2DM when compared to non-detectable VL (35). In the new era that calls for prompt HIV-1 diagnosis and linkage to care (the 90:90:90 initiative) (36), at least 27% of PLWH will continue to be viremic and thus at high risk for T2DM.…”
Section: Discussionmentioning
confidence: 93%
“…In their recent editorial regarding our paper, Drs Höner zu Siederdissen and Mederacke state that “it is well established that hepatitis C virus (HCV) monoinfected patients have a higher frequency of diabetes mellitus (DM), which may be caused by direct viral effects as well as lifestyle characteristics. In human immunodeficiency virus (HIV)/HCV coinfected patients mixed results have been observed regarding the association with DM.”…”
mentioning
confidence: 94%
“…In conclusion, our results are not only in keeping with some other studies performed among HIV/HCV‐co‐infected patients, but they are also in line with findings in HCV‐mono‐infected patients . In addition, we underline that the major strength of our study was to evaluate, in the same analysis and—to the best of our knowledge—for the first time, not only HCV serology status or chronic HCV infection, but also major HCV covariates, in particular the duration of HCV infection and cirrhosis, which is a major confounding factor for DM.…”
mentioning
confidence: 99%